2018
DOI: 10.1142/s2010135x1850011x
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of magnetoelastic interactions in Raman spectra of HoxNd1−xFe3(BO3)4 crystals

Abstract: Raman spectra of Ho[Formula: see text]NdxFe(BO3)4 ([Formula: see text], 0.75, 0.5, 0.25) have been studied in temperature range 10–400[Formula: see text]K. Two compositions ([Formula: see text], [Formula: see text]) demonstrate structural phase transition with soft mode restoration. The addition of Nd atoms increases interatomic spacing and decreases the temperature of structural phase transition. The solid solutions ([Formula: see text], 0.5, 0.25) demonstrate the emergence of the peaks corresponding to magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
12
1
5
Order By: Relevance
“…Параметры решетки определялись путем измерения брэгговских пиков (600) и (006) в функции от температуры при энергии фотона 10 keV и с помощью кристалла анализатора LiF (200). интенсивностей линий D3 и Gr5−D3 видно, что они исчезают при температуре ∼ 200 K, что хорошо согласуется с температурой структурного перехода, полученной в работе [15].…”
Section: образцы и экспериментыunclassified
See 2 more Smart Citations
“…Параметры решетки определялись путем измерения брэгговских пиков (600) и (006) в функции от температуры при энергии фотона 10 keV и с помощью кристалла анализатора LiF (200). интенсивностей линий D3 и Gr5−D3 видно, что они исчезают при температуре ∼ 200 K, что хорошо согласуется с температурой структурного перехода, полученной в работе [15].…”
Section: образцы и экспериментыunclassified
“…Для полноты картины на рис. 9 представлено изменение положения линии структурной мягкой моды в кристалле Ho 0.75 Nd 0.25 Fe 3 (BO 3 ) 4 в зависимости от температуры, взятое из работы [15]. Изменение положения мягкой моды также происходит скачком.…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Mode identification can be done by indexing the Raman peak positions but it may contain lot more information than simple chemical bonds energies which may also be investigated using IR spectroscopy, of course with certain limitations. Beyond the peak position of a Raman peak, the overall line shape of the spectrum is equally important as it may reveal several important physical phenomena taking place at microscopic level like quantum confinement or size effect, electron-phonon effect, fantum effect etc [9][10][11][12][13][14][15][16][17]. Apart from direct evidences, as a consequence of Raman line-shape's sensitivity towards external conditions, perturbations induced by temperature, pressure etc also can be investigated using classical and advanced Raman techniques [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Spin-lattice interactions such as magnetostriction and spin-lattice relaxation, are well known in spectroscopy, with numerous recent reports of spin-phonon coupling in the Raman spectra of several systems. 15,16,17,18,19,20 Four characteristic features of these accounts are that (i) they frequently involve spin states with differences (spin gap) of the order of meV (10 K), and hence are effective at low temperature, (ii) the differences in the spectra are small, typically a few cm -1 , (iii) they refer to periodic magnetism, at least within Individual domains, where collective effects are important, and (iv) they appear to be confined to systems containing transition metal or rare-earth components. More recently, Webster et al 21 reported the calculated Raman spectra of 2-dimensional ferromagnetic (FM) and antiferromagnetic (AFM) CrI 3 , where difference in energy between the two spin states was found to be 150 -160 K with shifts in frequency of up to 10 cm -1 , although the spectral profiles are much the same.…”
Section: Introductionmentioning
confidence: 99%